Gender-Responsive Zakat Management for Women’s Empowerment in Post-Crisis Revocery: A Conceptual Framework - Muhammad Romi; Hendri Sayuti; Nana Sepdiana; Adamu Abubakar Muhammad (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study examines the strategic role of zakat in promoting gender equality and strengthening women’s empowerment in post-crisis recovery contexts. The research is motivated by the increasing economic vulnerability of women during crises and the limited integration of gender perspectives in zakat governance. Employing a qualitative approach through library research, this study synthesizes evidence from academic literature, institutional reports, and prior empirical findings related to gender-responsive zakat management. The analysis is conducted using a thematic framework focusing on economic empowerment, social participation, inclusive governance, and policy integration. The findings indicate that zakat has significant potential to enhance women’s economic capacity through productive distribution schemes, entrepreneurship support, and access to Islamic microfinance. In addition, zakat contributes to strengthening women’s social roles and leadership within community and institutional settings. However, the study also identifies structural challenges, particularly the absence of comprehensive gender mainstreaming frameworks, limited data-driven evaluation mechanisms, and weak policy alignment. This study proposes a gender-responsive zakat optimization model based on four key pillars: gender-based budgeting, women’s representation in decision-making, cross-sector collaboration, and the digitalization of zakat services. Theoretically, this research contributes to the development of Islamic social finance literature by integrating gender equality perspectives into zakat discourse. Practically, it offers policy-oriented insights for zakat institutions and stakeholders to foster inclusive and sustainable socio-economic transformation.